Rekayasa Model Kelembagaan Kemitraan Ubikayu di Provinsi Lampung - Wan Abbas Zakaria; Lidya Sari Mas Indah; Teguh Endaryanto; Lina Marlina; Muhammad Ibnu (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
This study aims to analyze cassava partnerships in Lampung Province, analyze how partnerships can work effectively in terms of institutions and management, and analyze the cassava farmer partnership engineering models in Lampung. The method used in this research is descriptive qualitative with an in-depth interview method. The research locations were in Gunung Agung Village, Central Lampung Regency, and Labuhan Ratu Village, East Lampung, considering that they were the largest cassava centres in Lampung. The research was conducted in July 2019. The research data consisted of primary and secondary data with a total sample of 126 cassava farmers. The data were analyzed descriptive-qualitatively, namely the performance of several alternative institutional partnerships for cassava agribusinesses that are compatible with the characteristics of the participants and the commodities produced. The results show that a good partnership includes arrangements within the jurisdictional limits of the cassava agribusiness system, which is determined by the operating capacity per unit of tapioca mill that is permitted in a clear and firm zone, assistance by the third party to build a sense of togetherness between farmers and entrepreneurs also to induce loyalty, commitment, and integrity. The partnership engineering of cassava agribusinesses that is expected to be effective is a partnership built jointly by farmers (Farmers' groups and Gapoktan) and tapioca industry entrepreneurs mediated by a third party (Local Government or Universities or other agencies).